Analisis Peran Humas Melalui Guest Experience Leader Dalam Meningkatkan Pelayanan Di Mcdonald’s Bengkulu - Muhammad Afif Syaputra; Sapta Sari; Maryaningsih Maryaningsih (Universitas Dehasen Bengkulu, 2024)
This research aims to find out the role of Public Relations through the Guest Experience Leader (GEL) in improving service at McDonald's Bengkulu. This research is qualitative research. To analyze the researcher used Ruslan Efendi's theoretical analysis technique (Communicator, Relationship, Back Up Management and Corporate Image). The research results show that there is a role for GEL in improving service at McDonald's Bengkulu. GEL plays a role as a communicator who can ensure customers get a good impression during their visit to McDonald's Bengkulu, GEL's role as a Relationship Shop GEL must be able to build positive relationships through a good approach to customers and mutual benefits, GEL's role as Back Up Management GEL must be able to inspire, motivating and providing team training if necessary so they can work better, as Corporate Image GEL plays a role in maintaining the good name of the company as best as possible